2010
DOI: 10.1523/jneurosci.5604-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Striatal Dopamine Transmission and Motor Performance with LRRK2 Overexpression in Mice Is Eliminated by Familial Parkinson's Disease Mutation G2019S

Abstract: PARK8/LRRK2 (leucine-rich repeat kinase 2) was recently identified as a causative gene for autosomal dominant Parkinson's disease (PD), with LRRK2 mutation G2019S linked to the most frequent familial form of PD. Emerging in vitro evidence indicates that aberrant enzymatic activity of LRRK2 protein carrying this mutation can cause neurotoxicity. However, the physiological and pathophysiological functions of LRRK2 in vivo remain elusive. Here we characterize two bacterial artificial chromosome (BAC) transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
352
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(382 citation statements)
references
References 51 publications
26
352
4
Order By: Relevance
“…Consistent with this partial loss-of-function pathogenic mechanism, expression of various mutant forms of LRRK2 in mice, even at more than 10-fold of overproduction, has so far failed to reproduce PD-like neuropathological changes, such as cell death and α-synuclein aggregation (35)(36)(37)(38). Interestingly, a recent report showed that LRRK2 inactivation alleviated rather than exacerbated α-synuclein aggregation and neurodegeneration under overexpression conditions (>16-fold) in α-synuclein transgenic mice (37).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this partial loss-of-function pathogenic mechanism, expression of various mutant forms of LRRK2 in mice, even at more than 10-fold of overproduction, has so far failed to reproduce PD-like neuropathological changes, such as cell death and α-synuclein aggregation (35)(36)(37)(38). Interestingly, a recent report showed that LRRK2 inactivation alleviated rather than exacerbated α-synuclein aggregation and neurodegeneration under overexpression conditions (>16-fold) in α-synuclein transgenic mice (37).…”
Section: Discussionmentioning
confidence: 97%
“…31,32 As shown in Figure 2, robust concentration-dependent knockdown of phospho-LRRK2 (pLRRK2) levels in the brain was observed after ip dosing at 10 or 15 mg/kg. Inhibition modeling indicates the in vivo unbound brain IC 50 of 18 to be 12 nM.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 95%
“…Two transgenic mouse models overexpressing human G2019S LRRK2 exhibit modest age-dependent DA neuron loss associated with accumulation of autophagosomes and mitochondrial alterations [124,125], but other G2019S LRRK2 transgenic mouse models had diminished dopamine transmission and motor deficits without detectable neuron loss [53,54]. The only I2020T LRRK2 transgenic mouse model reported to date exhibits no obvious loss of DA neurons [126].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…The physiological function of LRRK2 is unknown, but LRRK2 is involved in autophagy [49,50], vesicle sorting and trafficking [51,52], dopamine homeostasis [53,54], dopamine receptor activation, synaptogenesis [55], and cytoskeleton dynamics (Fig. 2) [56,57].…”
Section: Introductionmentioning
confidence: 99%